(untitled) (Journal of Economic Research & Business Administration, 2015)
Problems further formation and development of market relations and the insurance market in Kyrgyzstan is seen as a transition from nonmarket to market-based society. This problem appears in the political, socio-economic as well as national and state level. Study of insurance business is currently an important factor in shaping the economic system of the state.